Demographic and Socio-economic Factors Affecting Fertility in Madhesh Province - Ale, Manawata (Kutumbha vani, 2023)
This study used secondary data from the 2022 Nepal Demographic and Health Survey (NDHS) to explore factors affecting fertility among 2,499 women in Madhesh province. The mean number of children ever born (CEB) in Madhesh was 2.21, higher than the national average of 1.86. The findings revealed higher fertility rates, larger household sizes, and younger age profiles in Madhesh compared to national averages. Education levels were lower, and the ages at first cohabitation and childbirth were earlier. Significant positive relationships were found between fertility and factors such as age, breastfeeding, child mortality, ideal number of children, and household size. In contrast, fertility was negatively associated with wealth, desired number of children, household head age, and pregnancy status. Furthermore, female household headship, the husband’s age, and the husband’s occupation positively affected fertility, while the husband’s education level had a strong negative effect. The study suggests that targeted programs addressing these factors are needed to reduce fertility rates and meet Sustainable Development Goals (SDGs) in Madhesh province. Factors such as religion, ethnicity, place of residence, age at first cohabitation, age at first birth, contraceptive use, abortion, respondents’ education and occupation, amenorrhoeic status, marriage-to-first-birth interval, and employment in the last twelve months were found to be non-influential.